New ways of visualization in laparoscopic surgery - Bartłomiej Grobelski; Dominik A. Walczak; Zbigniew Pasieka (Videosurgery and Other Miniinvasive Techniques)
Scientific achievements enabled tremendous progress of surgical minimally invasive methods in the 20th century.Laparoscopy and endoscopy became everyday diagnostic and therapeutic tools of modern medicine. Despite itsirrefutable opportunities and advantages, classical minimally invasive surgery still has substantial limitations. Theseinclude: two-dimensional visualization without depth, a small field of view, and the necessity of precise hand-eyecoordination. That is why pressure is placed on manufacturers of endoscopic devices to surmount these technicalobstacles. To write this paper we searched databases for articles on new means of visualization in laparoscopicsurgery. We discuss augmented reality, three-dimensional vision and image-guided surgery.